Workplace Discrimination Laws and Talent Retention in MNCs: Unpacking the Legal Risk Management Nexus - Khaddam, Amineh A.; Alzghoul, Amro; Irtaimeh, Hani J. (International Review of Management and Marketing, 2025)
This study examines how compliance with workplace anti-discrimination laws affects talent retention practices in multinational corporations operating in Jordan. Adopting a legal risk management perspective, we propose that adhering to discrimination legislation not only mitigates legal liabilities but also fosters an inclusive work environment that enhances employee retention. A quantitative survey design was used to get 194 answers from MNC subsidiaries in Jordan. We used structural equation modeling (SEM) to see if the relationships we thought were there were real. The results show that following workplace discrimination laws more closely is strongly linked to better talent retention outcomes. In addition, it was found that legal risk management practices made this relationship less strong: MNCs with better legal risk management saw a bigger positive effect of legal compliance on retention. This finding implies that compliance is even more advantageous when risk management is done proactively. According to these results, initiatives that support employees in abiding by the law may make them feel more committed and equitable, which may lessen their desire to quit the organization. This is particularly true when active risk management frameworks support these programs. By combining research on risk management, regulatory compliance, and human resource management (HRM), the study advances theory. Additionally, it advances practice by demonstrating that emerging market multinational corporations can retain their workforces by strategically aligning HRM with legal requirements.